Comparing Postcolonial Literatures
XI, 283 p.
Keywords: Bringing together a range of critics working on the hispanic and francophone as well as anglophone post-colonial regions, this book aims to dislocate some of the commonly accepted cultural, linguistic and geographical boundaries that have previously informed post-colonial studies. Collected essays include: cross-cultural comparisons from areas as diverse as Africa, Ireland and Latin America; analysis of specific texts as sites of border conflict; and revisions of post-colonial theoretical frameworks. A timely questioning of the categories of a critical field at the point when it is becoming increasingly comparative, this volume seeks to suggest more dynamic ways of working in post-colonial cultural studies.